PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) PADA BEBERAPA KOMPOSISI MEDIA TANAM DAN PEMBERIAN Trichoderma sp. - Deni Tri Prabowo; Rugayah Rugayah; Akari Edy; Muhammad Nurdin (Universitas Lampung, 2026)
Shallots (Allium ascalonicum L.) are one of the important horticultural commodities that often experience unstable harvest yields due to land quality degradation triggered by the massive and continuous use of chemical inputs. This study aims to identify the effect of planting media and Trichoderma sp. on the growth process and productivity of Bima Brebes shallots. This study was arranged in a two-factorial Randomized Block Design (RBD) (3 x 4) with three replications. The first factor was the media composition (soil, sand, rice husk charcoal, and goat manure). The second factor was Trichoderma sp. with doses of 0, 7.5, 15, and 22.5 g/polybag. The results of this study showed that the planting media treatment had a significant effect on almost all observed parameters. The use of media enriched with goat manure (C2 and C3) was able to increase the variables of plant height, number of leaves, bulb weight, bulb diameter, and root weight. The C2 medium showed the highest wet bulb yield of 31.54 g/polybag, while the C1 medium showed the lowest yield of 15.92 g/polybag. Conversely, the administration of various doses of Trichoderma sp. showed no effect on any of the observed parameters, and the two treatments showed no interaction. This is likely due to the low organic matter content, which limited the colonization of biological agents. The growth and yield of shallot bulbs were more optimal through the addition of media amendments such as goat manure to improve chemical and physical properties compared to the single application of Trichoderma.